Embryonic and larval development of endangered Temoleh, Probarbus jullieni (Sauvage) - Zakaria, Mohd Hazmadi; Sarker, S. M. Nurul Amin Harmuj Ali; Rahman, Md. Aminur; Mahmud, Muhammad Hatta; Christianus, Annie; Siraj, Siti Shapor; Arshad, Aziz (Academic Journals, 2013)
The present study was carried out to investigate the embryonic and larval development of the endangered Temoleh, Probarbus jullieni in lab-rearing condition. The matured egg and sperm were collected by stripping the bloodstock of Temoleh fish after injecting with ovaprim hormone extract. The samples were collected from hatching tank at every 10 min interval for the first hour, 20 min for the second hour, 30 min for the third hour and then hourly interval up to hatching. After hatching, larvae were observed daily until the complete disappearance of the yolk sacs. The fertilized eggs were spherical, demersal, adhesive and brownish-yellow in colour with a mean diameter of 2316 μm. First cleavage occurred within 10 min post-fertilization at temperature ranged from 26.0 to 28.0°C. Hatching started 22 h post-fertilization and completed within 25 h at the same temperature. The yolk sac was completely absorbed 61 h after hatching. At the same time, the larvae started to swim actively and feed exogenously. This marks the first description on the early life history of P. jullieni. The present study will provide some valuable information on the ontogeny, breeding biology and early larval rearing protocol of P. jullieni which will ultimately be helpful towards the establishment of large scale seed production technique for conservation and aquaculture production.